Answer:
Step-by-step explanation:
x+ 8/4 -x+ 5/4
= x+2+-x +5/4
Combine Like Terms:
x+2+-x+ 5/4
(x+x)+ ( 2 +5/4)
= 13/4
Answer:
(4,0) and (- 2,0): Answer
Step-by-step explanation:
Absolute value questions have two essential steps.
1. Solve the equation as it is written.
2. Solve it changing the sign of the right hand side. I will include a graph to confirm my answer
4*abs(x - 1) = 12 Divide by 4
- abs(x - 1) = 12/4
- abs(x - 1) = 3 Equate this to 3
- x - 1 = 3 Add 1 to both sides
- x - 1 + 1 = 3 + 1 Combine
- x = 4
4*abs(x - 1) = - 12 Divide by 4
- abs(x - 1) = - 12/4
- abs(x - 1) = - 3
- x - 1 = - 3 Add 1 to both sides
- x - 1 + 1 = -3 + 1
- x = - 2
So this has 2 answers
(4,0) and (- 2,0)
It is a i think sorry if wrong